Harlequin Ichthyosis: a rare congenital dermatological disorder - Sharma, Charu; Bhattacharyya, Tapan K.; Bhardwaj, Abhishek; Mehrotra, Manju (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Harlequin Ichthyosis is the most severe form of congenital Ichthyosis presenting at birth. It is a very rare disorder with autosomal recessive inheritance. Perinatal mortality is high and the survivors develop severe erythroderma subsequently. We report a case of Harlequin Ichthyosis not only because of its rarity but also its tendency to occur in consecutive pregnancies.